Identification of the Type IX Secretion System Component, PorV (CHU_3238), Involved in Secretion and Localization of Proteins in Cytophaga hutchinsonii - Zhao, Dong; Song, Wenxia; Wang, Sen; Zhang, Weican; Zhao, Yue; Lu, Xuemei (Frontiers in Microbiology, 2021)
Cytophaga hutchinsonii can efficiently degrade cellulose and rapidly glide over surfaces, but the underlying mechanisms remain unclear. The type IX secretion system (T9SS) is involved in protein secretion and gliding motility, which is unique to the phylum Bacteroidetes. In this study, we deleted a homologous gene of PorV (chu_3238), a shuttle protein in the T9SS. The Δ3238 mutant caused cellulolytic and gliding defects, while the porV deletion mutants in other Bacteroidetes could glide normally. Adding Ca2+ and K+ improved growth in the PY6 medium, suggesting a potential role of chu_3238 in ion uptake. Proteomic analysis showed an increase in the number of extracellular proteins in the Δ3238 mutant, and a decrease in the outer membrane proteins compared to the wild type (WT). Endoglucanase activity in the Δ3238 intact cells was reduced by approximately 70% compared to that of the WT. These results indicate that the secreted proteins could not attach to the cell surface but were released into the extracellular space in the Δ3238 mutant. However, the cargo proteins accumulated in the periplasm of other reported porV deletion mutants. In addition, the homologs of the translocon SprA and a Plug protein were pulled down by co-immunoprecipitation in the 3238-FLAG strain, which are involved in protein transport in the T9SS of Flavobacterium johnsoniae. The integrity of the lipopolysaccharide (LPS) was also affected in the Δ3238 mutant, which may be the reason for the sensitivity of the cell to toxic reagents. The functional diversity of CHU_3238 suggests its important role in the T9SS of C. hutchinsonii and highlights the functional differences of PorV in the T9SS among the Bacteroidetes.